An integrated model of statistical process control and maintenance based on the delayed monitoring - Yin, Hui; Zhang, Guojun; Zhu, Haiping; Deng, Yuhao; He, Fei (Reliability engineering & system safety, 2015)
This paper develops an integrated model of statistical process control and maintenance decision. The proposal of delayed monitoring policy postpones the sampling process till a scheduled time and contributes to ten-scenarios of the production process, where equipment failure may occur besides quality shift. The equipment failure and the control chart alert trigger the corrective maintenance and the predictive maintenance, respectively. The occurrence probability, the cycle time and the cycle cost of each scenario are obtained by integral calculation; therefore, a mathematical model is established to minimize the expected cost by using the genetic algorithm. A Monte Carlo simulation experiment is conducted and compared with the integral calculation in order to ensure the analysis of the ten-scenario model. Another ordinary integrated model without delayed monitoring is also established as comparison. The results of a numerical example indicate satisfactory economic performance of the proposed model. Finally, a sensitivity analysis is performed to investigate the effect of model parameters. •We develop an integrated model of statistical process control and maintenance.•We propose delayed monitoring policy and derive an economic model with 10 scenarios.•We consider two deterioration mechanisms, quality shift and equipment failure.•The delayed monitoring policy will help reduce the expected cost.